Exogenous melatonin treatment affects ascorbic acid metabolism in postharvest ‘Jinyan’ kiwifruit - Luo, Zhenyu; Zhang, Jieru; Xiang, Miaolian; Zeng, Jiaoke; Chen, Jinyin; Chen, Ming (Frontiers in Nutrition, 2022)
Ascorbic acid (AsA) is an important nutritious substance in fruits, and it also can maintain the biological activity of fruits during storage. This research investigated the effect of exogenous melatonin (MT) on AsA metabolism in postharvest kiwifruit. Our results indicated that exogenous MT delayed the decrease of fruit firmness and titratable acid (TA), inhibited the increase of soluble solids content (SSC), reduced the respiration rate and ethylene production, and maintained a higher AsA content in kiwifruit during storage. The high expression of L-galactose pathway key genes in the early storage and regeneration genes in the later storage maintained the AsA content in postharvest kiwifruit. MT treatment enhanced the expression levels of AsA biosynthesis (AcGME2, AcGalDH, and AcGalLDH) and regeneration (AcGR, AcDHAR, and AcMDHAR1) genes. Meanwhile, the expression of the degradation gene AcAO was inhibited in MT-treated kiwifruits.